TEKNIK PENYUTRADARAAN DENGAN GAYA EKSPOSITORI PADA PRODUKSI FEATURE “RAMBATING SUMBUT” - Falahul Alfiah; Dwi Nurrahmi Kusumastuti; Fadeyanto Prabowo (Jurnal Ilmu Komunikasi AKRAB, 2020)
This feature work, entitled Rambating Sumbut, tells about the problems that exist in the agricultural sector, particularly regarding farmer regeneration. As one of the food buffer areas in Bantul Regency, Imogiri sub-district has great agricultural potential, supported by existing natural resources. However, several unfavorable conditions had a significant impact on the agricultural sector in Imogiri District. Now the agricultural sector in Imogiri Subdistrict depends on unproductive peasants, of course this affects the quality of rice cultivation and crop yields.Many young people in Imogiri Subdistrict prefer to work in other sectors, besides that also because there are still old thoughts that say that farmers' children must get more work than farmers, in the hope of improving the family economy. Thus there needs to be an effort to regenerate farmers, to maintain the sustainability of agriculture and the survival of the next generation. The main thing that needs to be done is to change the mindset of young people who still regard the farmer profession as a job that does not promise the future. By integrating agriculture and existing technological developments, one of which is implementing integrated agriculture.